Partial Information Relaying with Per Antenna Superposition Coding - Kim, Dong In; Choi, Wan; Seo, Hanbyul; Kim, Byoung-Hoon (IEEE transactions on communications, 2010)
In this letter we propose per antenna superposition coding (PASC) by which partial information can be relayed instead of full information, to exploit the higher capacity of source-relay-destination link. Here, the PASC is designed across antennas, producing basic layer and superposed layer for each data stream per antenna. It is shown that an overall data rate of partial information relaying with PASC can be increased beyond that offered by full information relaying by virtue of fast forwarding of partial information over relatively better link.